DESENTRALISASI FISKAL DAN INKLUSIFITAS PERTUMBUHAN EKONOMI DIKABUPATEN/KOTA DI NTB - Ahmad Murad (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
This study aims to analyze Fiscal Decentralization and Inclusive Economic Growth in Regencies / Cities in NTB. The research variables used in the analysis include PAD and inclusive economic growth. Analysis of inclusive economic growth is carried out using a classy approach which includes poverty reduction, decreasing economic inequality and employment. Whereas the direction of the PAD's relationship to inclusive economic growth is done using a simple regression analysis model using the OLS method. While the data used is district / city panel data in NTB Province which covers a period of 4 years (2013-2016). The results of the analysis show that there was no inclusive economic growth in the Regency / City in NTB both in terms of poverty reduction, economic inequality and employment. Inclusive economic growth can only be enjoyed by the upper middle class, while the lower classes cannot benefit from economic growth. Meanwhile, on the other hand the role of fiscal decentralization through the use of PAD cannot affect inclusive economic growth both in terms of reducing poverty and decreasing economic inequality except in increasing employment. Where PAD influences inclusive economic growth through employment. This is due to the small contribution of PAD to economic development which only reached 8 percent during the research period that has not been able to reach all levels of society.